Les organisations logistiques à promouvoir dans le cadre des Politiques de Transport Durable de Marchandises : la question des circuits de proximité - Amélie Gonçalves (Développement Durable et Territoires)
Among the many virtues associated with short supply chains, the reduction of transport and logistics needs and the use of alternative coordination process are considered as potential positive effects for sustainable transport policies. This article aims at questioning this affirmation by studying different types of short supply chains, in several sectors. To do so, we will study the factors that determine the choices concerning transport and logistics in these chains, using a framework based on the theories of Proximities and Conventions. This will help us understand in which measure the logics and organisations in these chains can or could lead to more sustainable choices concerning transport and logistics, and could be exemplary schemes for sustainable transport policies.